A Path to Implement Precision Child Health Cardiovascular Medicine - Touma, Marlin; Reemtsen, Brian; Halnon, Nancy; Alejos, Juan; Finn, J. Paul; Nelson, Stanley F.; Wang, Yibin (Frontiers in Cardiovascular Medicine, 2017)
Congenital heart defects (CHDs) affect approximately 1% of live births and are a major source of childhood morbidity and mortality even in countries with advanced healthcare systems. Along with phenotypic heterogeneity, the underlying etiology of CHDs is multifactorial, involving genetic, epigenetic and/or environmental contributors. Clear dissection of the underlying mechanism is a powerful step to establish individualized therapies. However, the majority of CHDs are yet to be clearly diagnosed for the underlying genetic and environmental factors, and even less with effective therapies. Although the survival rate for CHDs is steadily improving, there is still a significant unmet need for refining diagnostic precision and establishing targeted therapies to optimize life quality and to minimize future complications. In particular, proper identification of disease associated genetic variants in humans has been challenging and this greatly impedes our ability to delineate gene-environment interactions that contribute to the pathogenesis of CHDs. Implementing a systematic multileveled approach can establish a continuum from phenotypic characterization in the clinic to molecular dissection using combined next generation sequencing (NGS) platforms and validation studies in suitable models at the bench. Key elements necessary to advance the field are: first, proper delineation of the phenotypic spectrum of CHDs; second, defining the molecular genotype/phenotype by combining whole exome sequencing and transcriptome analysis; third, integration of phenotypic, genotypic and molecular datasets to identify molecular network contributing to CHDs; fourth, generation of relevant disease models and multi-leveled experimental investigations. In order to achieve all these goals, access to high-quality biological specimens from well-defined patient cohorts is a crucial step. Therefore, establishing a CHD-Bio Core is an essential infrastructure and a critical step on the path towards precision child health cardiovascular medicine.